Multiple Fluorescences in Situ Hybridization Status in Excreted Urine Improve Diagnostic Efficacy for Upper Urinary Tract Urothelial Carcinomas - Tang, Feng; Wang, Xia; Liu, Tao; Wang, Hao; Wan, Ziyu; Fu, Qiqi; Zheng, Zhangjie; Aersi, Madanyeti; Peng, Jianping (Urology Journal, 2024)
Purpose: To evaluate the diagnostic accuracy of single and multiple fluorescence in situ hybridization (FISH) tests for upper urinary tract cancer (UTUC), we analyzed the diagnostic efficacy of FISH in patients with UTUC and the difference between it and the Tumor Node Metastasis (TNM) stage and grade of the tumor. Materials and Methods: Patients treated for UTUC at our institution between 2011 and 2021 who had not been previously diagnosed with UTUC were included. Patients were divided into single, two, and multiple (three times or four times) FISH groups based on the number of FISH tests performed on different samples from the same patient, and the diagnostic efficiency of single, two, and multiple FISH tests for muscle-invasive tumors and highgrade tumors were assessed. Results: We included a total of 207 patients with UTUC, and when compared to single FISH, the sensitivity of multiple and double FISH for the diagnosis of UTUC increased from 62% to 76% and 78%, respectively. It went from 67% to 78% and 80% for muscle-invasive UTUC (> = pT2) and from 71% to 79% and 81% for the highest- grade UTUC. Conclusion: Multiple FISH improves the diagnostic efficacy of UTUC and helps to differentiate aggressive tumors.